Manajemen Partisipatif Warga Sekolah Dalam Pengembangan Budaya Religius Peserta Didik - Rubiati Rubiati (Muslim Heritage, 2016)
Abstract: The religious culture is a form of religious teaching values that appear in the way a person behaves. In the context of educational institutions, religious culture appear in the organizational culture, followed by all the people in the school. So that the religious culture need to be developed through effective participative (participatory) management. Participative management is intended to empower the school community to the fullest involvement in the management of religious culture development programs. This study aimed to describe, analyze and explain the application of school community participative management in the development of religious culture of students in SMAN I Kwadungan. This study produced three findings: first, the development program of religious culture of learners are formulated based on the vision and mission of the school, which is further manifested in the six activities, namely: Islamic clothing (uniforms), giving smile, a greeting, obligatory prayer in congregation, Friday prayer, reading Al-Qur'an and infaq. Second, the application of participative management school community in the development of religious culture was done by involving people in schools ranging from decision-making, implementation, benefit to the evaluation. Thirdly, By applying participative management, school community gives a good response in the form of positive attitudes and actions, and fully contribute to supporting the development of religious culture.Abstrak: Budaya religius merupakan wujud nilai-nilai ajaran agama yang tampak dalam cara berperilaku seseorang. Dalam konteks kelembagaan pendidikan, budaya religius tampak dalam budaya organisasi yang diikuti oleh seluruh warga di sekolah. Agar budaya religius benar-benar menjadi cara berperilaku baik individu maupun organisasi, perlu dikembangkan melalui manajemen partisipatif yang efektif. Manajemen partisipatif dimaksudkan untuk memberdayakan keterlibatan warga sekolah secara maksimal dalam pengelolaan program-program pengembangan budaya religius. Penelitian ini bertujuan untuk mendeskripsikan, menganalisis dan menjelaskan tentang penerapan manajemen partisipatif warga sekolah dalam pengembangan budaya religius peserta didik di SMAN I Kwadungan. Penelitian ini menghasilkan tiga temuan: pertama, program pengembangan budaya religius peserta didik dirumuskan berdasar pada visi dan misi sekolah, yang selanjutnya diwujudkan dalam enam kegiatan, yaitu: busana (seragam) Islami, memberi senyum, menyapa, sholat fardhu berjamaah, sholat jumat, membaca Al-Qur’an dan infaq.  Kedua, penerapan manajemen partisipatif warga sekolah dalam pengembangan budaya religius dilakukan dengan melibatkan warga sekolah mulai dari proses pengambilan keputusan, pelaksanaan, memperoleh manfaat sampai dengan evaluasi. Ketiga, Dengan menerapkan manajemen partisipatif,  warga sekolah memberikan respon yang baik yang berupa sikap dan tindakan positif, serta berkontribusi dalam mendukung pelakasnaan pengembangan budaya religius peserta didik.